1995
DOI: 10.1016/0014-5793(94)01326-v
|View full text |Cite
|
Sign up to set email alerts
|

Differential penetration of fatty acyl‐coenzyme A and fatty acylcarnitines into phospholipid monolayers

Abstract: The ability of fatty acyl-CoA's and fatty acylcarnitines to penetrate phospholipid monolayers was comparatively studied, in view of the important role of both kinds of derivatives in fatty acid transport across mitochondrial membranes. The interaction occurs predominantly through hydrophobic forces. Acylcarnitines penetrate phospholipid monolayers more strongly than acyl-CoAs; in addition the former show a positive cooperativity when they bind to the interface. These properties would facilitate membrane transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 10 publications
2
25
1
Order By: Relevance
“…The same tendency was shown with the bis-derivatives with lysine. The results obtained in this study confirm that the increase of the hydrophobic forces is in favour of the penetration into lipidic monolayers [18,27].…”
Section: Influence Of the Chain Length Of The Fatty Acid (8 12 Or 14)supporting
confidence: 82%
See 1 more Smart Citation
“…The same tendency was shown with the bis-derivatives with lysine. The results obtained in this study confirm that the increase of the hydrophobic forces is in favour of the penetration into lipidic monolayers [18,27].…”
Section: Influence Of the Chain Length Of The Fatty Acid (8 12 Or 14)supporting
confidence: 82%
“…This interaction maintains the molecules in the monolayer even at surface pressure higher than those attained after simple adsorption at the interface. If there was no interaction, the derivatives would fill the empty spaces in the DPPC monolayer only until reaching their adsorption equilibrium pressure [16,27]. Furthermore, increasing the chain length enhances the capacity of penetration into the DPPC monolayer.…”
Section: Influence Of the Chain Length Of The Fatty Acid (8 12 Or 14)mentioning
confidence: 99%
“…However, a thorough study by Constantinides and Stein [2] indicated that the the critical micelle concentration for palmitoyl-CoA can be as high as 70-80 µM under physiological conditions. Acyl-CoA esters partition into phospholipid vesicles by insertion of the hydrophobic acyl chain into the bilayer [4][5][6][7]. The partition constant for palmitoyl-CoA in phospholipid vesicles can be calculated from the original data of Peitzsch and McLaughlin [5] to be 1.5i10& M −" , and a value of 5i10& M −" has also been determined directly [7].…”
Section: Physical Properties Of Long-chain Acyl-coa Esters and Their mentioning
confidence: 99%
“…More recently, Requero et al [5] described the influence of electrolytes and other factors on the critical micellar concentrations and other pertinent properties of acylcarnitines. Finally, Requero et al [6] have provided direct measurements, using a Langmuir-type balance, of the increase in surface pressure that occurs at the air-water interface when palmitoylcarnitine is injected in the bulk of the solvent. In addition, when the air-water interface is initially covered by a monomolecular layer of phospholipids (e.g.…”
Section: Palmitoylcarnitine As a Surfaetantmentioning
confidence: 99%
“…In addition, when the air-water interface is initially covered by a monomolecular layer of phospholipids (e.g. egg phosphatidylcholine), injection of palmitoylcarnitine in the solvent is followed by penetration of the carnitine derivative into the phospholipid monolayer, a lateral stabilisation arising from the interaction between both lipids [6].…”
Section: Palmitoylcarnitine As a Surfaetantmentioning
confidence: 99%